Perkembangan Sikap Sosial Anak melalui Proses Apresiasi terhadap Tradisi Sambatan di Desa Dermolo, Jepara - Wahyu Candra; Deka Setiawan; Nur Fajrie (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2020)
This research aims to describe the Sambatan Tradition in DermoloVillage, the values of character education and influence on children’s social behavior through an appreciation process. This research uses descriptive method with a phenomenological approach. The object of this research is the Sambatan Tradition in Dermolo Village, while the subject is the Dermolo Village community. The targets of this research are the Sambatan Traders, Dermolo Village community leaders, SDN 03 Dermolo principals, teachers and students. Data obtained through in-depth interview, observation, documentation and recording. There are two sources of data in this research, namely the Dermolo Village community who are directly involved with the Sambatan Tradition and education practitioners at SDN 03 Dermolo including students. Validity test uses source triangulation techniques. Data analysis techniques using data reduction, data presentation and conclusion or verification. The Sambatan Tradition with character education value has a great influence on the lives of the people of Dermolo Village and encourages the appreciation of children. Sustainability of the Sambatan Tradition with values of tolerance, social care and environmental care implied in it has an influence on children’s development, especially social attitudes in daily life. Keywords: Sambatan Tradition, appreciation, character, social attitudes of children